2013
DOI: 10.1007/s10147-013-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid profile index for early detection of endometrial cancer: verification as a novel diagnostic marker

Abstract: The sensitivity and disease specificity of API for early-stage detection of endometrial cancer was superior to CA125. This novel plasma biomarker has the potential to become a diagnostic and screening marker for endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 21 publications
4
58
0
2
Order By: Relevance
“…59 As summarized in Table 1, Gly consumption was pronounced in pancreatic cancer, 27 breast cancer, 28, 29 colorectal cancer 41 and cervical cancer. 42 While Ser levels were high in some patients with pancreatic cancer, 20 breast cancer, 31, 32 lung cancer, and colorectal cancer, 29 probably due to the overexpression of phosphoglycerate dehydrogenase, other cancers, such as colorectal cancer, 21, 27, 42 pancreatic cancer, 27 gastric cancer 28 and cervical cancer 43 consumed Ser. Although Ser and Gly could be inter-converted and either of them might be used for one-carbon metabolism and nucleotide synthesis, convincing evidence suggested that cancer cell proliferation were supported by Ser instead of Gly consumption.…”
Section: Mechanism Underlying Alterations Of Pfaa Profilesmentioning
confidence: 99%
“…59 As summarized in Table 1, Gly consumption was pronounced in pancreatic cancer, 27 breast cancer, 28, 29 colorectal cancer 41 and cervical cancer. 42 While Ser levels were high in some patients with pancreatic cancer, 20 breast cancer, 31, 32 lung cancer, and colorectal cancer, 29 probably due to the overexpression of phosphoglycerate dehydrogenase, other cancers, such as colorectal cancer, 21, 27, 42 pancreatic cancer, 27 gastric cancer 28 and cervical cancer 43 consumed Ser. Although Ser and Gly could be inter-converted and either of them might be used for one-carbon metabolism and nucleotide synthesis, convincing evidence suggested that cancer cell proliferation were supported by Ser instead of Gly consumption.…”
Section: Mechanism Underlying Alterations Of Pfaa Profilesmentioning
confidence: 99%
“…The Fischer index (the ratio of branched chain amino acids to aromatic amino acids) is a useful indicator for diagnosis and prediction of liver diseases [5]. Previous studies have shown that several cancers, including lung, gastric, colorectal, breast and prostate cancer, influence plasma free amino acid profiles, and measuring these profiles accurately could be a valuable diagnostic tool [6][7][8][9][10][11]. Furthermore, plasma free amino acid profiles are also associated with visceral fat accumulation in obese Japanese subjects [12].…”
Section: Introductionmentioning
confidence: 97%
“…At the same time, it was convincingly demonstrated that the removal or correction of the intermediate metabolic changes can be achieved using individual amino acids and their derivatives or a combination of them as universal natural bioregulators -compounds that has direct effect on the mechanisms of cellular metabolism in physiological concentrations [1][2][3]. To date, there are evidences of the importance of not only amino acids as building blocks for protein synthesis, but regulators of gene expression at the level of mRNA translation by mTOR-dependent mechanism, signaling molecules and bio-logical response modifiers, as well as, precursors of a wide range of bioregulators, which play a key role in the integration of major metabolic fluxes [12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%